L-Lactate Electrochemical Biosensor Based on an Integrated Supramolecular Architecture of Multiwalled Carbon Nanotubes Functionalized with Avidin and a Recombinant Biotinylated Lactate Oxidase - Tamborelli, Alejandro (2024)
Factor Impacto: 4.9 (2023); 5-Años Factor Impacto: 5.2 (2023)